2021
DOI: 10.1177/2056305120984445
|View full text |Cite
|
Sign up to set email alerts
|

Online Engagement Between Opposing Political Protest Groups via Social Media is Linked to Physical Violence of Offline Encounters

Abstract: The rise of the Internet and social media has allowed individuals with different backgrounds, experiences, and opinions to communicate with one another in an open and largely unstructured way. One important question is whether the nature of online engagements between groups relates to the nature of encounters between these groups in the real world. We analyzed online conversations that occurred between members of protest groups from opposite sides of the political spectrum, obtained from Facebook event pages u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 85 publications
1
28
0
Order By: Relevance
“…According to his result, disinformation spread by governmental actors and political parties contributes to domestic terrorism but the effect is mediated by political polarization and tribalism within countries. Rather similar results were recently obtained also by Gallacher et al (2021) according to whom discussions in social media between opposing groups are associated with offline physical violence. A relation has been also found between online hate speech and offline hate crimes (Williams et al 2020).…”
Section: Introductionsupporting
confidence: 86%
“…According to his result, disinformation spread by governmental actors and political parties contributes to domestic terrorism but the effect is mediated by political polarization and tribalism within countries. Rather similar results were recently obtained also by Gallacher et al (2021) according to whom discussions in social media between opposing groups are associated with offline physical violence. A relation has been also found between online hate speech and offline hate crimes (Williams et al 2020).…”
Section: Introductionsupporting
confidence: 86%
“…The articles in this special issue reinforce common knowledge that when individuals with diverse views and values engage on social media the outcomes range from negative and harmful (Gallacher et al, 2020) to positive and hopeful (Ron et al, 2020). Which of these outcomes results depends on a combination of the intent of social media participants, the level of reflection and self-awareness users consider as they post and respond, and the design of social media platforms themselves.…”
Section: Looking Forwardmentioning
confidence: 67%
“…While their case study demonstrates communication is not always dialogic, their examination of a sample of posts and responses in the Facebook group represents the potential for dialogue when groups come together with dialogic intentions. However, Gallacher et al (2020) studied social media interaction in which members from opposing political protest groups engaged on each other's Facebook events pages, resulting in harmful, rather than helpful, communication. In fact, their study demonstrated that interaction on social media predicted violence in offline encounters-such as when the protest events took place.…”
Section: The Good and The Bad Of Online Discussionmentioning
confidence: 99%
“…In doing so, they have boosted the volume and the diversity of news content, opinion, and commentary available to local, regional, and national audiences (Shah et al 2017;Van Aelst et al 2017). This has also led many political content producers, from journalistic organizations to political parties, candidates during elections, interest groups, and individual citizens to shift "from serving mass audiences to niche audiences (Stroud 2011), with their content morphing away from inclusive, consensus-oriented messages to exclusive, conflictoriented [and sometimes extreme or polarizing political] messages (Mutz 2015)" (Shah et al 2017: 494;Gallacher et al 2021).…”
Section: Contextualizing Contemporary Political Appealmentioning
confidence: 99%